The Influence of Epistemological Beliefs and Dispositions on the Development of Critical Thinking - Maria V. Solodikhina (Вопросы образования)
Empirical studies of various pedagogical influences aimed at the development of critical thinking have revealed a problem — regardless of the approach and teaching methods, approximately the same proportion of students who do not demonstrate improvement in their critical thinking skills are recorded. It is suggested that the "critical thinking" construct contains elements that are not usually taken into account in teaching, but which influence the desire of students to develop their critical thinking skills and apply them.